Planning Cities in Africa
XXI, 243 p. 37 illus., 26 illus. in color.
Keywords: This open access book provides insights into challenges, threats and opportunities of urban development in Africa. It discusses how and why African cities need localised urban planning concepts and theories to deal with challenges and threats of rapid urbanisation and climate change. The book delivers an in-depth view of the nature and gaps of the framework on which current planning practice and education in Africa are based. With that, it discusses the potentials of African cities to mobilise local knowledge, resources and capacity building for sustained and resilient urban growth. This work is addressed to educationists and practitioners in the field of urban development management, climate change adaptation and urban resilience. Specifically, such audiences include researchers, spatial planners, graduate students and member of civil societies working on urban development management.